The Present of Anaphoric and Cataphoric Reference in the Novel Entitled Persuasion by Jane Austen - Luthfi Nasiroh Khoirun Nisa; Rahmaditya Khadifa Abdul Rozzaq Wijaya; Aris Hidayatulloh (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Language serves as a crucial instrument for shaping communication and fostering understanding across diverse contexts. Effective text organization can prevent misunderstandings, making a deep understanding of English text systems and structures essential. Discourse analysis, which examines language use in social contexts to create meaning and facilitate communication, is vital for appreciating the subtleties of language and the strategies employed by speakers and writers. This study focuses on the role of references within discourse. Using Jane Austen’s Persuasion as a data source, this research applies Halliday and Hasan’s (1976) framework to analyze the types of anaphoric and cataphoric references. Through a descriptive qualitative methodology and document analysis, the study identifies a higher frequency of anaphoric references compared to cataphoric ones. This analysis provides insights into Austen’s storytelling techniques.